2020
DOI: 10.1057/s41599-020-0397-4
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, human capital and ethnic occupational niches: an analysis of ethnic and gender inequalities in the Spanish labour market

Abstract: This article analyses the role of different types of social capital in the integration of immigrants into the labour market of Catalonia (Spain), according to the geographical distribution and ethnic characteristics of immigrants' contacts. It aims to test the role of social networks, human capital and the ethno-stratification of the labour market in immigrants' labour market performance; and to contribute to understanding the often overlooked but complex interactions between these factors and gender inequalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(51 reference statements)
0
7
0
1
Order By: Relevance
“…Larger networks may have more potential to provide support, but they are more likely to increase conflict and negative effects on immigrants' lives due to the pressure, responsibility and restrictions originating from the intense involvement and ties among certain social networks (Gellis, 2003). Additionally, high-density ethnic group networks may centralize the immigrant labor force within ethnic occupational niches, and the exchange of solidarity and information through social networks keeps migrants in occupational positions similar to those held by other ethnic group members (Bolíbar, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger networks may have more potential to provide support, but they are more likely to increase conflict and negative effects on immigrants' lives due to the pressure, responsibility and restrictions originating from the intense involvement and ties among certain social networks (Gellis, 2003). Additionally, high-density ethnic group networks may centralize the immigrant labor force within ethnic occupational niches, and the exchange of solidarity and information through social networks keeps migrants in occupational positions similar to those held by other ethnic group members (Bolíbar, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this study, the support that immigrant women trainees receive includes support from their Taiwanese family and friends, their natal family, ethnic friends in Taiwan, and the government. Some research has suggested that social support networks with ethic groups and intimate families in host countries are an important mechanism for improving immigrants' career development, including employability (i.e., the accumulation of human capital and work adaptation) (Bolíbar, 2020) and employment quality (i.e., security of employment, work duties, and work earnings) (Debono & Vassallo, 2020).…”
Section: Ssmentioning
confidence: 99%
“…(Mujer, Bulgaria, Comarca 3) Las trayectorias de progreso inmigrante tienen que ver también con la consecución de una cierta estabilidad y formalidad laboral ("tener nóminas") y una vivienda para así poder reagrupar al cónyuge y los hijos menores. Es una doble trayectoria de progreso laboral y vital-familiar, en el transcurso de la cual se confirma la importancia de establecer redes de confianza con españoles (Bolíbar, 2020) y eventualmente contar con la ayuda de autoridades locales, trabajadores sociales, miembros de ONG u otras personas dispuestas a ofrecer información y apoyo de todo tipo. El éxito parece depender mucho, aparte de la suerte, de la disposición a asumir los costes físicos y emocionales de la aventura migratoria, y, obviamente, la mayor o menor dificultad para residir y trabajar legalmente de forma estable que tienen los diferentes grupos nacionales, de la consistencia de la red de apoyo que la persona inmigrante encuentre a su llegada.…”
Section: El Medio Rural En Los Proyectos Y Trayectorias Migratoriasunclassified
“…Therefore, native employees are preferred in the labor market, and employers are reluctant to recognize migrants as potential workers in their labor sector. Employers may therefore ignore the trainability of their human capital abilities, such as career-related skills, language, and other aspects of their occupational status, increasing, over time, in the receiving country (Bolíbar 2020). On the other hand, migrants think that their labor market skills are usually conceptualized around the following three elements: first, the fact that their human capital skills are not perfect and have mainly been acquired in their country of origin; second, the selectivity factors from the destination country; and lastly, their economic gain in the destination country (Chiswick and Miller 2008).…”
Section: Occupational Status Of Migrantsmentioning
confidence: 99%